Characteristics of Project-Based Learning Models on the Project to Strengthening the Pancasila Student Profiles at Muhammadiyah School (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2024)
The Project for Strengthening the Pancasila Student Profile utilized a Project-based Learning (PjBL) approach, distinguishing it from intracurricular PjBL programs. The implementation of this project in schools remains complex due to its novelty and the ongoing search for an effective model for planning, implementation, and evaluation. The objectives of this study were as follows: (1) to describe the implementation of the PjBL model in the Project for Strengthening the Pancasila Student Profile at a Muhammadiyah junior high school in Batu City, (2) to describe the development of the Pancasila Student Profile after the implementation of the PjBL model in the Project for Strengthening the Pancasila Student Profile, and (3) to outline the challenges faced by the school and their corresponding solutions in implementing the PjBL model in the Project for Strengthening the Pancasila Student Profile. This research adopted a descriptive and qualitative approach. Data collection techniques encompassed in-depth interviews, observations, and documentation studies. The findings revealed that: (1) the implementation of the PjBL model in the Project for Strengthening the Pancasila Student Profile commenced with material mastery, followed by project execution, and concluded with a celebration, (2) the students demonstrated good character development in alignment with the Pancasila Student Profile, which consists of six competencies formulated as key dimensions, and (3) the encountered challenges in implementing the PjBL model in the Project for Strengthening the Pancasila Student Profile included difficulties in determining the appropriate time for implementing the P5 Project due to the teachers' busy schedules. In conclusion, the activities of the Project for Strengthening the Pancasila Student Profile, utilizing the PjBL approach, have been successfully carried out and have led to the formation of the Pancasila student profile, although there have been implementation obstacles. The best practices observed at Muhammadiyah Middle School in Batu City can serve as an inspiration for other Muhammadiyah schools and private institutions. Widespread implementation of such practices poses a challenge for future researchers.